Soy β-conglycinin improves obesity-induced metabolic abnormalities in a rat model of nonalcoholic fatty liver disease. Issue 2 (March 2015) - Wanezaki, Satoshi; Tachibana, Nobuhiko; Nagata, Mayuko; Saito, Shintaro; Nagao, Koji; Yanagita, Teruyoshi; Kohno, Mitsutaka
Summary Nonalcoholic fatty liver disease (NAFLD) has a variety of causes including calorie over-intake, an unbalanced diet, and/or genetic dysfunction of lipid metabolism. We hypothesized that NAFLD symptoms could be mitigated by specific nutritional factors. Here, we show that the potential for soy β-conglycinin (βCG) to improve obesity-induced metabolic abnormalities in the Otsuka Long Evans Tokushima fatty (OLETF) rat model of NAFLD. Long Evans Tokushima Otsuka (i.e., wild-type) and OLETF rats were provided a normal diet containing 20% casein for 4 weeks as a control. In a third (βCG) group, OLETF rats were fed a diet in which half of the casein was replaced by βCG. There was no difference in food intake between groups. Rats in the βCG group had decreased liver weight and lipid content (triglycerides, cholesterol, and phospholipids) compared to controls. In addition, βCG consumption decreased fatty acid synthase gene expression and enzymatic activity. These findings indicate that dietary intake of βCG can improve obesity-induced metabolic dysfunction, possibly via suppression of de novo fatty acid synthesis.